Chama o personal : estudo etnográfico sobre consultorias pessoais - Dios, Maria Luísa Célia Escalona de (2017)
In the last ten year, Brazil has shown an increase on its purchasing power, a relative growth of social mobility and also of sophisticated consumption.In parallel to those processes, there was an increment upon the offering of personal services which turned into the form of consultancies to accomplish several activities, such as sorting out closets, walking dogs, shopping, advising on customer´s way of dressing and building his/her personal image, among others.Individuals that provide such sort of services call themselves personals, emphasizing the individual nature of supplied services. Since those professionals hold a especific know-how they introduce themselves as "specialists".Their given services meet demands that did not exist until short time ago or were met by other means. Therefore, they were met by the individual himself as long as he held the needed knowledge and skills, got through familiar socialization or by some other family member, through friends or employees who held those skills, which means that those services were supplied in the scope of wider and steady relatioships,involving the logic of gift or those relationships based on wageearning. From a research developed between 2013 and 2016 in Porto Alegre, Sao Paulo and Paris, this thesis aims to investigate the rise of that personal services market.Using an ethnographic approach one searched to see how offering and the demand for such personal services were built and what the implications were in the way the individual was developed into contemporaneity.The main conclusion for this work says the formation of that personal services market is related to changes in the family life organization and in the professional work environment and specific in the Brazilian case, to the economic upswing of certain social groups and also with the possibility of capital reconversion by specific social segments and professional categories.